A multidisciplinary evaluation of robotic-assisted surgery effectiveness and its implications for healthcare education and practice - review of literature - Korus , Justyna; Hopej, Natalia; Grzegorczyk, Aleksandra; Dardzińska, Nicol; Dziedziak, Marta (Journal of Education, Health and Sport, 2025)
The following work is a review of the literature on the use of robots in the operating room in various fields of surgery. Due to the progress of medicine and technology, the management of a patient requiring surgery is changing and new technologies are increasingly being used, including robotic surgery and the da Vinci robot. They have found application in various fields of surgery, such as urology, gynecology, general surgery, and cardiothoracic surgery, examples of which are described in the following work. Both its positive aspects, which include precision, better visibility of the operating field and the possibility of visualization in 3D HD technology, have been discussed. On the other hand, there are also negative aspects such as the need for specialist staff training and the cost of surgery using a robot. All of the above should be taken into account when qualifying the patient for the method of performing the surgery and considering the possible benefits that he or she is able to achieve. The use of this treatment method requires an individual approach and the determination of specific indications and contraindications to ensure the greatest possible safety and the best possible outcome.